PLACE AND PURPOSE OF THE POLICE INSTITUTION IN THE GLOBALIST SYSTEM OF DEREGULATION - Anđelković, Stefan (Political Review, 2024)
Based on its pre-modern roots, and apparently in its new century, modern meaning, the police represent the protection of the state, that is, a guarantee of its sovereignty. The modern organization of the state itself implies the existence of the police, which guarantees the constitutional order, that is, defends the existing system of social organization. Globalization implies, however, a narrowing of the autonomy of nation-states. Free flow of capital, goods, people, and services - requires de-sovereignation, i.e., reduction of decision-making power in national states. The question arises - does this change the role of the police, i.e., does the police still have the primary task of preserving the sovereignty of the state, or is it now directed towards the goal - the free flow of capital and the preservation of the world economic order (free market), which has a supranational character. This paper contributes to the understanding of the mentioned problem.